2013
DOI: 10.1095/biolreprod.113.111542
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Testosterone Induces Sex-Specific Dysfunction in Endothelium-Dependent Relaxation Pathways in Adult Male and Female Rats1

Abstract: Prenatal testosterone (T) exposure impacts postnatal cardiovascular function, leading to increases in blood pressure with associated decreased endothelium-dependent vascular relaxation in adult females. Endothelial function in males is not known. Furthermore, which of the endothelial pathways contributes to endothelial dysfunction and if there exists sex differences are not known. The objective of this study was to characterize the relative contribution of nitric oxide (NO) and endothelium-derived hyperpolariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 53 publications
4
29
1
Order By: Relevance
“…The present study confirms our previous finding that prenatal T exposure induces hypertension and impairs the endothelial EDHF component of vasodilation in resistance arteries [17] and expands on it by demonstrating that this impairment is reversed by enalapril treatment. In addition, we have demonstrated that enalapril specifically restored the expression and function of the Kcnn3 channel in mesenteric arteries of prenatal T-exposed rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study confirms our previous finding that prenatal T exposure induces hypertension and impairs the endothelial EDHF component of vasodilation in resistance arteries [17] and expands on it by demonstrating that this impairment is reversed by enalapril treatment. In addition, we have demonstrated that enalapril specifically restored the expression and function of the Kcnn3 channel in mesenteric arteries of prenatal T-exposed rats.…”
Section: Discussionsupporting
confidence: 91%
“…It is of importance to note that endothelial dysfunction is shown to be a common denominator to all types of hypertension regardless of its pathogenesis [15]. Decreased generation of EDHF, which is particularly critical in resistance arteries, has been shown to contribute to impaired endothelium-dependent vasodilation in genetic as well as developmentally programmed hypertension [16][17][18][19][20][21][22][23]. Recently, a reduced expression of Kcnn3 channel mRNA, but not Kcnn4, was observed in mesenteric arteries of rats programmed to develop hypertension following prenatal exposure to testosterone (T) [17].…”
mentioning
confidence: 99%
“…DHT group rats were implanted with DHT pellets (7.5-mg, 90-d release) for 10 weeks, and control rats were implanted with matched placebo pellets. This dose and duration of DHT were selected to mimic 2-fold increases in androgen levels in PCOS females [21][22][23][24][25]. At the end of the 10 weeks experimental period, rats were subjected to glucose tolerance test and then sacrificed by CO 2 inhalation.…”
Section: Dihydrotestosterone Treatment and Animal Carementioning
confidence: 99%
“…Interestingly, treatment of various animals prenatally with testosterone produces the metabolic as well as reproductive disorders associated with PCOS [2][3][4][5][6][7][8][9]. The metabolic defects associated with prenatal androgen exposure are not limited to females, but are also seen in males [2,10,11]. Likewise, hypertension and insulin resistance are not only associated with PCOS, but also with metabolic syndrome which impacts both males and females.…”
Section: Introductionmentioning
confidence: 99%